Actin in Dividing Cells: Contractile Ring Filaments Bind Heavy Meromyosin - Schroeder, Thomas E. (1973)
Many microfilaments and microtubules are well preserved after glycerol-extraction of HeLa cells at room temperature (22°). Incubation in heavy meromyosin from rabbit skeletal muscle results in conspicuous and characteristic “decoration” of microfilaments of the contractile ring. Decoration is completely prevented by 10 mM ATP or 2 mM pyrophosphate, and fails to occur if heavy meromyosin is either omitted or replaced by egg albumin, a nonspecific protein. Decorated microfilaments have a substructure consisting of polarized, repeating arrowheads 27-35 nm apart. The specificity of these results strongly suggests that microfilaments of the contractile ring in HeLa cells are closely related to muscle actin. Very thin undecorated strands among the microfilaments of the contractile ring possibly represent a myosin component. These findings are discussed in terms of: the actomyosin-like properties of the contractile ring as a mechanochemical organelle that causes cell cleavage; the probable universal occurrence of actin-like protein in all dividing animal cells; and the contractile ring's combined sensitivity to cytochalasin B and its affinity for heavy meromyosin, a combination unique among microfilamentous organelles.